The influence of age and gender on motor and non-motor features of early Parkinson's disease: initial findings from the Oxford Parkinson Disease Center (OPDC) discovery cohort. - Szewczyk-Krolikowski, K; Tomlinson, P; Nithi, K; Wade-Martins, R; Talbot, K; Ben-Shlomo, Y; Hu, M (2014)
BACKGROUND: Identifying factors influencing phenotypic heterogeneity in Parkinson's Disease is crucial for understanding variability in disease severity and progression. Age and gender are two most basic epidemiological characteristics, yet their effect on expression of PD symptoms is not fully defined. We aimed to delineate effects of age and gender on the phenotype in an incident cohort of PD patients and healthy controls from the Oxford Parkinson Disease Centre (OPDC). METHODS: Clinical features, including demographic and medical characteristics and non-motor and motor symptoms, were analyzed in a group of PD patients within 3 years of diagnosis and a group of healthy controls from the OPDC cohort. Disease features were stratified according to age and compared between genders, controlling for effects of common covariates. RESULTS: 490 PD patients and 176 healthy controls were analyzed. Stratification by age showed increased disease severity with age on motor scales. Some non-motor features showed similar trend, including cognition and autonomic features. Comparison across genders highlighted a pattern of increased severity and greater symptom symmetricality in the face, neck and arms in men with women having more postural problems. Amongst the non-motor symptoms, men had more cognitive impairment, greater rate of REM behavior disorder (RBD), more orthostatic hypotension and sexual dysfunction. CONCLUSIONS: Age in PD is a strong factor contributing to disease severity even after controlling for the effect of disease duration. Gender-related motor phenotype can be defined by a vertical split into more symmetrical upper-body disease in men and disease dominated by postural symptoms in women.